∫ 0 π / 2 tan 3 ( x ) cos 5 ( x ) cos ( 7 x ) d x = B A
The equation above holds true for some coprime positive integers A and B . Find A + B .
Bonus : Find the close form of the definite integral, I Y , Z = ∫ 0 π / 2 ( tan ( x ) ) Y ( cos ( x ) ) Z − 2 cos ( Z x ) d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Isn't this approach 'not so helpful' for proving the Bonus ?
Log in to reply
Nope, there is another one involving beta function. Very long to write.
Typo: = ∫ 0 1 ( − 6 4 u 1 1 + 1 7 6 u 9 − 1 6 8 u 7 + 6 3 u 5 − 7 u 3 ) d u = − 1 2 6 4 u 1 2 + 1 0 1 7 6 u 1 0 − 8 1 6 8 u 8 + 6 6 3 u 6 − 4 7 u 4 ∣ ∣ ∣ 0 1
Log in to reply
Thanks a lot. I have done the changes.
Log in to reply
There's a typo on the integral part, at u 9
Log in to reply
@Hung Woei Neoh – Thanks again
Log in to reply
@Chew-Seong Cheong – You're welcome
Btw, may I ask, what is that B thing?
Log in to reply
@Hung Woei Neoh – Sorry, I have explained in the solution refer here: beta function and gamma function .
Sir can you provide the link for expansion of cos nx uses in the very 1st step of your solution
Use property of definite integration f(x)=f(a+b-x)
Problem Loading...
Note Loading...
Set Loading...
cos ( n x ) = ⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ k = 0 ∑ n ( 2 k n ) ( − 1 ) ⌊ 2 n ⌋ + k cos 2 k x sin n − 2 k x k = 0 ∑ n ( 2 k + 1 n ) ( − 1 ) ⌊ 2 n + 1 ⌋ + k cos 2 k + 1 x sin n − 2 k − 1 x if n is even if n is odd
Considering when n is odd:
I = ∫ 0 2 π tan m x cos n − 2 x cos n x d x = ∫ 0 2 π sin m x cos n − m − 2 x cos n x d x = ∫ 0 2 π sin m x cos n − m − 2 x k = 0 ∑ n ( 2 k + 1 n ) ( − 1 ) ⌊ 2 n + 1 ⌋ + k cos 2 k + 1 x sin n − 2 k − 1 x d x = ∫ 0 2 π k = 0 ∑ n ( 2 k + 1 n ) ( − 1 ) ⌊ 2 n + 1 ⌋ + k cos 2 k + n − m − 1 x sin m + n − 2 k − 1 x d x = k = 0 ∑ n ( 2 k + 1 n ) ( − 1 ) ⌊ 2 n + 1 ⌋ + k ∫ 0 2 π cos 2 k + n − m − 1 x sin m + n − 2 k − 1 x d x = 2 1 k = 0 ∑ n ( 2 k + 1 n ) ( − 1 ) ⌊ 2 n + 1 ⌋ + k B ( 2 2 k + n − m , 2 m + n − 2 k ) There must be a simpler general form.
Putting m = 3 and n = 7 , we have:
I = 2 1 k = 0 ∑ 7 ( 2 k + 1 7 ) ( − 1 ) k + 1 B ( k + 2 , 5 − k ) = 2 1 ( − 7 B ( 2 , 5 ) + 3 5 B ( 3 . 4 ) − 2 1 B ( 4 , 3 ) + B ( 5 , 2 ) ) = 7 B ( 3 , 4 ) − 3 B ( 2 , 5 ) = 7 ⋅ Γ ( 7 ) Γ ( 3 ) Γ ( 4 ) − 3 ⋅ Γ ( 7 ) Γ ( 2 ) Γ ( 5 ) = 7 ⋅ 6 ! 2 ! 3 ! − 3 ⋅ 6 ! 1 ! 4 ! = 6 0 7 − 1 0 1 = 6 0 1
⟹ A + B = 1 + 6 0 = 6 1
Previous solution
I = ∫ 0 2 π tan 3 x cos 5 x cos 7 x d x = ∫ 0 2 π sin 3 x cos 2 x T 7 ( cos x ) d x = ∫ 0 2 π sin x ( 1 − cos 2 x ) cos 2 x T 7 ( cos x ) d x = ∫ 0 1 ( 1 − u 2 ) u 2 T 7 ( u ) d u = ∫ 0 1 ( 1 − u 2 ) u 2 ( 6 4 u 7 − 1 1 2 u 5 + 5 6 u 3 − 7 u ) d u = ∫ 0 1 ( − 6 4 u 1 1 + 1 7 6 u 9 − 1 6 8 u 7 + 6 3 u 5 − 7 u 3 ) d u = − 1 2 6 4 u 1 2 + 1 0 1 7 6 u 1 0 − 8 1 6 8 u 8 + 6 6 3 u 6 − 4 7 u 4 ∣ ∣ ∣ ∣ 0 1 = 6 0 1 T n ( ⋅ ) is Chebyshev polynomial of the first kind Let u = cos x ⟹ d u = − sin x d x
⟹ A + B = 1 + 6 0 = 6 1